2017
DOI: 10.1080/02699052.2017.1283537
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in brain morphology from 4 weeks to 12 months after mild traumatic brain injury: Associations with cognitive functions and clinical variables

Abstract: Objective: To investigate longitudinal changes in cortical and subcortical volumes in patients with mild traumatic brain injury (MTBI) and to evaluate whether such changes were associated with self-reported post-concussive symptoms, global functional outcomes and neuropsychological functioning.Methods: This was a prospective, longitudinal cohort study of patients with complicated (i.e., presence of intracranial abnormalities on the day-of-injury CT) and uncomplicated MTBI (i.e., absence of intracranial abnorma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The relationship between altered pattern of functional connectivity and deficit cognition performance, especially in attention, executive function, and working memory has been supported in patients with mild TBI ( 10 , 52 54 ), however few studies investigated the correlation between changes in functional connectivity and changes in cognitive behavioral measures over a long time period ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between altered pattern of functional connectivity and deficit cognition performance, especially in attention, executive function, and working memory has been supported in patients with mild TBI ( 10 , 52 54 ), however few studies investigated the correlation between changes in functional connectivity and changes in cognitive behavioral measures over a long time period ( 55 , 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria for this study included the presence of severe mental illness (schizophrenia or bipolar disorder), progressive neurologic disease, ICD-10 diagnosis of substance dependence, contraindications for magnetic resonance imaging (MRI), and a lack of Norwegian language skills. We have previously reported brain volumetric and morphometric findings based on T1-weighted MRI data and DTI data in an overlapping sample [37][38][39], but not used brain-age prediction and not in relation to APOE status. Of the total sample of 168 patients at baseline, 134 (80%) patients returned for the 12-month follow-up visit, which included a clinical assessment and multimodal MRI; of these patients, 123 had available volumetric, APOE, and DTI data of sufficient quality.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…In addition, a T2-weighted sequence and a T2 susceptibility-weighted angiography sequence were performed to depict hemorrhagic or other lesions. No major scanner upgrade occurred during the study period and the cortical reconstruction and segmentation processes are described in previous articles [37,38].…”
Section: Mri Processingmentioning
confidence: 99%
“…Injury-related variables alone, such as loss of consciousness (LOC), post-traumatic amnesia (PTA), and neuroimaging findings, have limited value for predicting symptom burden (15,16). Several studies have also examined the differences between patients with confirmed intracranial injury seen on cerebral computer tomography (CT) or magnetic resonance imaging (MRI) (complicated mTBI) and those without (uncomplicated mTBI) (5,17). However, PPCS also frequently occurs in patients without traumatic radiological abnormalities (5,18).…”
Section: Introductionmentioning
confidence: 99%
“…However, PPCS also frequently occurs in patients without traumatic radiological abnormalities (5,18). Some studies have shown lower levels of postconcussion symptoms in patients with uncomplicated mTBI compared to complicated mTBI and moderate TBI (5,19,20), while others have found no differences between the groups (17,21). Iverson et al (16) found no significant difference in outcome when comparing complicated and uncomplicated mTBI, but effect sizes indicated more post-concussion and depressive symptoms in patients with uncomplicated mTBI.…”
Section: Introductionmentioning
confidence: 99%